(untitled) (Acta Judicial Journal, 2021)
The creation of a common framework at European level in succession matters with the approval of Regulation (EU) 650/2012, allow institutions of Catalan Civil Law such as the sacramental testament to favor the realization of the testator’s will regarding the ordination of his succession.